Field Trial of Local Nutrition Plans and Programs Monitoring and Evaluation Protocol in the Philippines - Africa, Leila S; Tandang, Nancy A.; Talavera, Ma. Theresa M. T.; Querijero, Nelson Jose Vincent B.; Carada, Wilfredo B.; Montecillo, Kristine V.; Bustos, Angelina R.; De Juras, Aileen R.; Amit, Mayo Grace C.; Gawe, Hygeia Ceres Catalina B.; Tandingan, Jasmine Anne F. (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2021)
The field trial was conducted to establish the reliability in producing similar results between evaluators of the proposed new tools for Monitoring and Evaluation (M&E) of the nutrition plans and programs in the Local Government Units (LGUs). To do this, orientation activities were conducted to familiarize the 46 M&E team (MET) members evaluating the provincial, municipal, city, and barangay levels in two regions with the proposed tools during the field trial. After the event, the perceptions of the MET members of the tools were gathered by asking them to rate the tools through a self-administered questionnaire, and by noting their written and verbal commentaries about the proposed system. During the field trial, each MET member, as well as the member of the Project Team (PT), individually evaluated the LGUs usingthe tools. Secondary data on the LGUs performance scores using the old system were also gathered. The MET members’ perception was examined based on the median rank of their ratings and content analysis of their insights about the tools, whereas the reliability of the tools was assessed based on the interrater reliability of the MET members’ scores for the LGUs analyzed through paired samples t-Test, Pearson correlation coefficient, intraclass correlation coefficient, and technical error of measurement. The weighted scores of the MET and PT members were also compared. Moreover, the difference in the generated scores between the old and the new system was determined. The findings revealed that the MET members generally have a positive perception of the new system but raised some issues and concerns. Although the reliability of the tools was generally observed, actions are warranted for improvement. The tools generated statistically different scores when used by MET and PT members, and when compared to the existing system. Steps should be taken to improve the reliability of the proposed tools.